Progress of nursing interventions on medication adherence in patients with hypertension (高血压患者服药依从性的护理进展) - LI Fang (李芳) (中西医结合护理)
Hypertension can affect the physical and mental health of older adults. This paper summarized the concept, research status, influencing factors and countermeasures of medication adherence in patients with hypertension, and provided reference for establishing nursing strategies on medication adherence in the treatment of hypertension. (高血压是老年人群中常见的心血管疾病, 严重影响老年人的身心健康和生活质量。本研究从高血压患者服药依从性的概念、国内外研究现状、影响因素及相应措施等方面进行综述, 以期为制定提高高血压患者服药依从性的相关护理措施提供参考。)